2017
DOI: 10.1016/j.soncn.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Family Caregiver Communication to Provide Family-Centered Cancer Care

Abstract: Objectives To describe a family caregiver communication typology and demonstrate identifiable communication challenges among four caregiver types: Manager, Carrier, Partner, and Lone. Data Sources Case studies based on interviews with oncology family caregivers. Conclusion Each caregiver type demonstrates unique communication challenges that can be identified. Recognition of a specific caregiver type will help nurses to adapt their own communication to provide tailored support. Implications for Nursing P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 35 publications
(34 reference statements)
1
29
0
Order By: Relevance
“…e study methods included semistructured interview, focus group study, and questionnaire survey. Study participants had been diagnosed with mixed cancer [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44], breast cancer [45][46][47][48][49], ovarian cancer [50], cervical cancer [51], melanoma [52], and head and neck cancer [53,54]. e details (study aims, study design, samples, cancer stage, instrument used, and key findings) can be seen in Table S2.…”
Section: Study Quality and Characteristics A Total Of 26 Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…e study methods included semistructured interview, focus group study, and questionnaire survey. Study participants had been diagnosed with mixed cancer [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44], breast cancer [45][46][47][48][49], ovarian cancer [50], cervical cancer [51], melanoma [52], and head and neck cancer [53,54]. e details (study aims, study design, samples, cancer stage, instrument used, and key findings) can be seen in Table S2.…”
Section: Study Quality and Characteristics A Total Of 26 Articlesmentioning
confidence: 99%
“…Eighteen studies covered the communication target needs of patients/caregivers. Out of this total, four studies reported the needs of caregivers [29,31,32,41], while 12 reported the needs of patients [30, 34-37, 40, 44, 48-52] and two reported the needs of both patients and caregivers [42,46]. Communication targets included healthcare professionals (n � 18, 69.2%), peers (n � 4, 15.4%), patients (n � 1, 3.8%), caregivers (n � 1, 3.8%), and others (n � 1, 3.8%).…”
Section: Findings On Communication Needsmentioning
confidence: 99%
“…Whilst care home staff do have a great deal of communication with residents' families, there has not been a need to research the notion of ' extending care' to settings beyond the care home, hence the lack of studies on this topic. However, transferable learning is offered by research in contexts such as hospices, intensive care units and palliative care (Bélanger et al, 2017;Kynoch et al, 2016;Petros and John, 2019;Schulman-Green and Feder, 2018;Gilissen et al, 2018;Wittenberg et al, 2017;Adams et al, 2017) who employ trained staff to offer counselling, bereavement counselling and spiritual care. This is not currently part of the portfolio of care-home services, although care home staff often do develop close relationships with residents and families and offer consolation and emotional support.…”
Section: Er3: Supporting Families At a Distancementioning
confidence: 99%
“…Few reports have investigated differences in caregiver communication behaviors about cancer, yet variance in interaction patterns among family members exist and greatly impact caregiver psychosocial morbidity, quality of life, and perceived social support . Specifically, communication research about cancer caregivers has found that there are four family caregiver communication types: manager, partner, carrier, and lone caregivers . The typology is based on interaction patterns for family communication that are dependent upon the relationship between the caregiver and patient and develop from implicit and explicit rules for communicating within the family system.…”
Section: Introductionmentioning
confidence: 99%
“…Interaction patterns are either high (strong) or low (weak) within the family and between the caregiver and patient. Each type is summarized briefly in Table . Caregiver communication types influence the scope of caregiving burden and inform the communication behaviors exhibited with health care providers …”
Section: Introductionmentioning
confidence: 99%